The Role of Teachers' Pedagogical Competence in Designing Deep Learning With Hots Assessment on Students' Critical Thinking Skills in Elementary School - Endang Setiyowati; Ari Metalin Ika Puspita; Neni Mariana (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study seeks to describe the role of teachers' pedagogical competence in designing deep learning that integrates Higher Order Thinking Skills (HOTS) assessment on critical thinking skills of elementary students. The research uses an exploratory sequential mixed-methods approach, with three teachers in grades 4, 5, and 6 at UPT SDN 232 Gresik as research subjects, and involved 78 students. Data collection was conducted through learning observations, in-depth interviews, analysis of Deep Learning Plan (RPM) documents, and HOTS assessments. The results reveal that teachers' pedagogical competence in designing deep learning was good, with variation across classes: Grade 4 and Grade 5 teachers demonstrated strong competence with consistent integration of HOTS, whereas the Grade 6 teacher indicated a significant gap between conceptual planning and classroom implementation. Teachers' ability to compile HOTS assessments also varied: the Grade 5 teacher produced the most balanced instrument, with 10 of 15 items at the C4-C6 level, while the Grade 6 teacher designed all 9 items at C4-C6 but with poor alignment between the teaching content and the assessment difficulty. Students' critical thinking skills showed significant variation across classes, with an overall average score of 75.72 (Good category): Grade 5 achieved the highest average of 86.86 (Very Good), Grade 4 achieved 75.74 (Good), and Grade 6 achieved the lowest at 64.58 (Adequate). This research recommends continuous training for teachers in designing authentic HOTS assessments and in ensuring alignment between lesson planning, classroom scaffolding, and assessment demands.